2006
DOI: 10.1007/s10620-006-9125-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Role of Endothelial Nitric Oxide Synthase (eNOS/NOS-III) in Cerulein-Induced Rat Acute Pancreatitis

Abstract: Nitric oxide (NO) is a potent pancreatic vasodilator, yet the pathogenic role of NO in acute pancreatitis remains controversial. NO is generated from L-arginine by NO synthase (NOS), classified into three isozymes: neuronal (nNOS), inducible (iNOS), and endothelial NOS (eNOS). The purpose of the present study was to investigate the role of NO/NOS isozymes in the pathogenesis of cerulein-induced acute pancreatitis in rats. Acute pancreatitis was induced in male Wistar rats by two subcutaneous injections of ceru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…However, baseline eNOS expression also remained unchanged throughout a 7-hour cerulein-induced AP timecourse experiment [16] . Another study found a markedly lower dimerization of eNOS [32] after 7 h of cerulein administration, which is associated with reduced eNOS activity [33] . A reduction in eNOS activity has been associated with disruption in the pancreatic microvascular blood flow [16] as well as increased expression of adhesion molecules on the endothelial cells of the blood vessels [34,35] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, baseline eNOS expression also remained unchanged throughout a 7-hour cerulein-induced AP timecourse experiment [16] . Another study found a markedly lower dimerization of eNOS [32] after 7 h of cerulein administration, which is associated with reduced eNOS activity [33] . A reduction in eNOS activity has been associated with disruption in the pancreatic microvascular blood flow [16] as well as increased expression of adhesion molecules on the endothelial cells of the blood vessels [34,35] .…”
Section: Discussionmentioning
confidence: 91%
“…The role of eNOS in pancreatitis has been getting more attention recently; studies have shown that pancreatic eNOS activity decreases during pancreatitis [16,32] . However, baseline eNOS expression also remained unchanged throughout a 7-hour cerulein-induced AP timecourse experiment [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Vasoactive mediators, such as bradykinin, platelet activating factor, endothelin and NO, participate in the development of pancreatic microcirculatory failure. Recently, in druginduced pancreatitis models, some researchers found that there is a correlation among NF-kappaB activation, serum amylase, reactive oxygen species level and tissue damage, suggesting that NF-kappaB and iNOS play a key role in the pathogenesis of acute pancreatitis [14][15][16] . After treatment with antioxidants or NOS inhibitors, the levels of myeloperoxidase, serum amylase and NO, as well as iNOS activities are decreased significantly, and the pancreatic inflammation is improved [14,15] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in druginduced pancreatitis models, some researchers found that there is a correlation among NF-kappaB activation, serum amylase, reactive oxygen species level and tissue damage, suggesting that NF-kappaB and iNOS play a key role in the pathogenesis of acute pancreatitis [14][15][16] . After treatment with antioxidants or NOS inhibitors, the levels of myeloperoxidase, serum amylase and NO, as well as iNOS activities are decreased significantly, and the pancreatic inflammation is improved [14,15] . Ma et al [16] found that the expression of NF-kappaB and iNOS in peritoneal macrophages is significantly higher in rats with severe acute pancreatitis, and anti-inflammatory agents decrease the expression of TNF-alpha, IL-1 and NO in peritoneal macrophages, reducing the severity of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects were attributed to the endothelial isoform by using the rather unspecific NOS inhibitor N -nitro-L-arginine methyl ester (L-NAME) without further dissecting a possible role of the neuronal isoform [16], [17].…”
Section: Introductionmentioning
confidence: 99%